A review of field hockey injuries and countermeasures for prevention - Sherker, S.; Cassell (Monash University Accident Research Centre, 1998)
Hockey is an ancient sport thought to be the forerunner of all `stick and ball` games. The modern game of hockey is played in 132 countries around the world and is second only in popularity to soccer as a team sport. Epidemiological studies have consistently shown that injuries in hockey are numerous and can be serious. Most serious injuries result from being struck by the stick or the ball. Overuse injuries to the ankles and lower back are also frequently reported. Players aged between 10 and 19 years account for 50% of all Victorian hospital emergency department presentations for hockey injuries. Most injuries presenting to hospitals are to the upper limb (mostly injuries to the hand and forearm), face (mostly struck by stick or ball) and lower limb (mostly ankle, foot and knee injuries). Injuries to the eyes are infrequent, although tend to be severe. The aim of this report is to critically review both formal research literature and informal sources of information in the context of the available epidemiological data, which describe preventive strategies and countermeasures to hockey injury. Countermeasures for preventing hockey injuries with some evidence to support effectiveness include: enforcing rules aimed at preventing dangerous use of the hockey stick and careless play of the ball; modifying rules for children; use of protective equipment (such as shin guards, eye wear and mouthguards); expert training of coaches and officials; adequate nutrition; pre-season conditioning; pre-game stretch and warm-up; prompt access to professional first aid and medical care; and full rehabilitation before returning to play. Potential countermeasures requiring further investigation include: risk management plans; prophylactic taping and bracing of ankles; altering the stick design to make it safer; the use of protective gloves; extending pre-season screening to include non-elite players; and improving injury data collection, especially for non-elite levels of play. A systematic program of epidemiological and biomechanical research is required to investigate these and other risk and preventive factors.